EFEKTIVITAS PENDAMPINGAN PEKERJA SOSIAL TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DI KABUPATEN BULELENG - Randy Ray Sinaga; Adnyani, Ni Ketut Sari; Yasmiati, Ni Luh Wayan (Jurnal Ilmu Hukum Sui Generis, 2024)
This research aims to determine (1) The role of social workers' companions (2) What factors influence social workers' assistance to victims of domestic violence. This type of research is empirical research, this empirical legal research is descriptive, using primary and secondary data collected through observation, interviews and document study, then analyzed qualitatively. The subjects in this research were social workers, investigators from the Buleleng Police PPA unit, Head of the Integrated Service Center for women and children at the P2KBP2A service and victims of domestic violence who were handled by social workers. The research results show that: (1) the role of social assistance is working well, this is demonstrated through the implementation of social assistance procedures in dealing with victims of Domestic Violence (KDRT). (2) influencing factors, such as the victim's physical and psychological trauma, continued violence, and limited access to government services and also human resources for social workers are still small because few people know about the existence of social workers.